Systematic Literature Review: Efektiftivitas Pendekatan Kontekstual untuk Meningkatkan Pemahaman Konsep Bilangan - Khusna, Akhmad Qoidul; Fuat, Fuat; Supriyo, Supriyo (Indo-MathEdu Intellectuals Journal, 2025)
The Contextual Teaching and Learning (CTL) approach is a learning strategy that connects subject matter with real-life contexts to enhance students’ understanding. This study aims to evaluate the effectiveness of the CTL approach compared to traditional methods in teaching number concepts, as well as to identify obstacles and optimal strategies for its implementation. The method used is a Systematic Literature Review (SLR) following the PRISMA framework. The articles analyzed were sourced from SINTA-accredited journals published between 2021 and 2025, and were examined using thematic analysis to identify key patterns in findings. The results show that the CTL approach significantly improves students’ mathematics learning outcomes, particularly in operations involving integers and fractions. The main challenges identified include teachers’ lack of understanding of the CTL method, limited availability of instructional aids, and differences in students’ abilities. Recommended strategies include teacher training, the development of learning media, and the implementation of differentiated instruction. The study also found that instructional aids are more effective than visual illustrations in teaching number concepts. Thus, the CTL approach holds significant potential for enhancing students’ mathematical understanding. The integration of technology and the development of contextual media are necessary to optimize implementation across diverse educational settings